Thematic Progression in Acehnese EFL Learner-Produced Texts - Risdaneva Risdaneva; Syarifah Dahliana (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2019)
This study reports the thematic progression of the EFL learner- produced texts in Acehnese context. The study employed qualitative method focusing on the content analysis. The content analysis technique was incorporated to analyse the corpora of 40 learner-produced texts. The findings of the study highlight both prevalent and problematic thematic progression patterns in the students’ texts. The EFL learners are inclined to use the constant theme pattern with less consistency of accuracy in longer paragraphs. With regard to the problematic patterns, the students tend to find difficulties in developing the ideas throughout the texts. This is shown through the emergence of many brand new themes and empty rhemes which result in incohesive and incoherent texts. The overall findings suggest that introducing the theme- rheme pattern concept to the students in English writing classes can be useful for improving the cohesion of the EFL students’ writings.